Incidence of dengue virus infection among Japanese travellers, 2006 to 2010 - Nakamura, Naomi (World Health Organization, 2012)
INTRODUCTION: Dengue continues to be a global public health concern. In Japan, although dengue cases are currently seen only among travellers returning from endemic areas, the number of reported cases is rising according to the national case-based surveillance system. We evaluated the characteristics of dengue cases imported into Japan and the relationship between the incidence of infection and season of travel to popular destinations. METHODS: Dengue cases reported to the national surveillance system were retrospectively examined. The number of reported cases per number of Japanese travellers to a dengue-endemic country was calculated to estimate the country-specific incidence of imported dengue virus infection. The incidence of dengue infection among Japanese travellers was compared between dengue high season and low season in each country using relative risk (RR) and associated 95% confidence intervals (CI). RESULTS: Among 540 Japanese residents who were reported as dengue cases from 2006 to 2010, the majority had travelled to Indonesia, India, the Philippines and Thailand. The RR of dengue infection among Japanese travellers during dengue high season versus low season was 4.92 (95% CI: 3.01–8.04) for the Philippines, 2.76 (95% CI: 1.67–4.54) for Thailand and 0.37 (95% CI: 0.15–0.92) for Indonesia. DISCUSSION: Overall, higher incidence of imported cases appeared to be related to historic dengue high seasons. Travellers planning to visit dengue-endemic countries should be aware of historic dengue seasonality and the current dengue situation.